If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y(5) + -2(2 + 7 + -18) = 0 Reorder the terms for easier multiplication: 9 * 5y + -2(2 + 7 + -18) = 0 Multiply 9 * 5 45y + -2(2 + 7 + -18) = 0 Combine like terms: 2 + 7 = 9 45y + -2(9 + -18) = 0 Combine like terms: 9 + -18 = -9 45y + -2(-9) = 0 Multiply -2 * -9 45y + 18 = 0 Reorder the terms: 18 + 45y = 0 Solving 18 + 45y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 45y = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 45y = 0 + -18 45y = 0 + -18 Combine like terms: 0 + -18 = -18 45y = -18 Divide each side by '45'. y = -0.4 Simplifying y = -0.4
| x=x^2-10x-11 | | 5y=12x-8 | | 20x+14y=3748 | | X(1-x)=0.02 | | 3x-9=3x+9 | | .5a^2+a-12=0 | | -4x-7(1-x)=-11x+9(3x+5) | | (x-3.5)^2/3=150 | | 32=5+-3t | | -1/2x+3=x-7 | | x=x+(.005n*x) | | (4x^2-3x^3)-(9x^2-5x^3)=-5x^2+2x^3 | | -4x-7(1-x)=11x+9(3x+5) | | -6x^2+64x+192=0 | | 4x^2+8x-26=(x+3)(x-2) | | 20x+10=80x+50 | | y=x+(.06*x) | | 6x+3=4x-13 | | z^2+6z-9=6z | | 3(x+6)=7x-14 | | -3x^2+32x+96=0 | | 2(0)-5x=10 | | (4x^2-3x^3)-(9x^2-5x^3)=-3x^5 | | y=x+(.005n*x) | | 4x-8=33 | | X(4x)=64 | | 1/3y=x | | 11+12k=-25 | | 3x+4+5x=20 | | z/10=13 | | 3(0)-2x=6 | | 10=5+2x^3 |